CXCR2 Receptor Antagonists: A Medicinal Chemistry Perspective - P. Dwyer, Michael; Yu, Younong (Current Topics in Medicinal Chemistry, 2014)
Dysregulated leukocyte recruitment is believed to be a key contributor to various acute and chronic inflammatory disorders which can lead to serious pathological consequences. Chemokines are small molecular weight proteins that have been shown to be imperative in the direction of leukocytes to the sites of inflammation. In humans, several of these chemokines (CXCL8 and CXCL1) are elevated in inflammatory disorders such as asthma, arthritis, and chronic obstructive pulmonary disease (COPD). These chemokines modulate their downstream effects thru G-protein coupled receptors, such as CXCR2, making the identification of small-molecule antagonists of this receptor attractive towards developing novel therapies to treat inflammatory conditions. Since the first report of a CXCR2 receptor antagonist in 1998, there has been a considerable effort conducted mainly in the pharmaceutical industry to identify novel classes of CXCR2 receptor antagonists. Over a dozen distinct classes of CXCR2 receptor antagonists have been reported in the literature to date with a number of these compounds having reached mid-stage clinical trials. This review will provide a broad overview the medicinal chemistry efforts over the past 15 years towards the identification of CXCR2 receptor antagonists. The discussion will focus upon the early preclinical space covering the structure activity relationships (SAR), pharmacology, as well in preclinical in vivo evaluation for the different series of CXCR2 receptor antagonists. In addition, the available clinical data for the most advanced compounds in the clinic will be discussed and along with a perspective of the area moving forward.
Keywords: Gro-α (CXCL1)